The concept of being healthy and sick from Scavengers’ point of view - Kokom Komariah, Hanny Hafiar, Priyo Subekti, Lukiati Komala, (Opción, 2019)
This study intends to examine the concept of being healthy and being sick from a scavenger’s point of view based on their intrapersonal communication process. The method used in this research is qualitative descriptive; data collected through observation, interview, and literature study. The results of the research show that the scavengers’ concepts of being healthy and being sick are relatively different from the ones accepted by society in general. In conclusion, in the campaigns, the activities arranged are appropriate for scavengers in terms of language and the depth of information shared.